Indispensable Role of CX3CR1+ Dendritic Cells in Regulation of Virus-Induced Neuroinflammation Through Rapid Development of Antiviral Immunity in Peripheral Lymphoid Tissues - Choi, Jin Young; Kim, Jin Hyoung; Hossain, Ferdaus Mohd Altaf; Uyangaa, Erdenebelig; Park, Seong Ok; Kim, Bumseok; Kim, Koanhoi; Eo, Seong Kug (Frontiers in Immunology, 2019)
A coordinated host immune response mediated via chemokine network plays a crucial role in boosting defense mechanisms against pathogenic infections. The speed of Ag presentation and delivery by CD11c+ dendritic cells (DCs) to cognate T cells in lymphoid tissues may decide the pathological severity of the infection. Here, we investigated the role of CX3CR1 in the neuroinflammation induced by infection with Japanese encephalitis virus (JEV), a neurotrophic virus. Interestingly, CX3CR1 deficiency strongly enhanced susceptibility to JEV only after peripheral inoculation via footpad. By contrast, both CX3CR1+/+ and CX3CR1-/- mice showed comparable susceptibility to JEV following inoculation via intranasal and intraperitoneal routes. CX3CR1-/- mice exhibited lethal neuroinflammation after JEV inoculation via footpad route, showing high mortality, morbidity, proinflammatory cytokine expression, and uncontrolled CNS-infiltration of peripheral leukocytes including Ly-6Chi monocytes and Ly-6Ghi granulocytes. Furthermore, the absence of CX3CR1+CD11c+ DCs appeared to enhance susceptibility of CX3CR1-/- mice to JE after peripheral JEV inoculation. CX3CR1 ablation impaired the migration of CX3CR1+CD11c+ DCs from JEV-inoculated sites to draining lymph nodes (dLNs), resulting in decreased NK cell activation and JEV-specific CD4+/CD8+ T-cell responses. However, CX3CR1-competent mice showed rapid temporal expression of viral Ags in dLNs. Subsequently, JEV was rapidly cleared, with concomitant generation of antiviral NK cell activation and T-cell responses mediated by rapid migration of JEV Ag+CX3CR1+CD11c+ DCs. Using biallelic functional CX3CR1 expression system, the functional expression of CX3CR1 on CD11chi DCs appeared to be essentially required for inducing rapid and effective responses of NK cell activation and Ag-specific CD4+ T cells in dLNs. Strikingly, adoptive transfer of CX3CR1+CD11c+ DCs was found to completely restore the resistance of CX3CR1-/- recipients to JEV, as corroborated by the rapid delivery of JEV Ags in dLNs and attenuation of neuroinflammation in the CNS. Collectively, these results indicate that CX3CR1+CD11c+ DCs play an important role in generating rapid and effective responses of antiviral NK cell activation and Ag-specific T cells after peripheral inoculation with the virus, thereby resulting in conferring resistance to viral infection by reducing the peripheral viral burden.